Version [2.0] - [VIC-Borg: Multiobjective automatic calibration toolkit for VIC model] - Jinfeng Ma; Hua Zheng; Ruonan Li; Kaifeng Rao; Yanzheng Yang; Weifeng Li (SoftwareX)
The VIC-Borg tool facilitates multi-objective automatic calibration for the variable infiltration capacity (VIC) model, but its efficiency was constrained by single-machine performance. To enhance calibration efficiency, we developed a parallelized, distributed optimization tool using MPI. It orchestrates computing tasks, enabling multiple VIC simulations per node while preventing result overwrites. Case studies demonstrate that the tool achieves a speedup of 31 using 50 computing cores, significantly enhancing performance. This tool simplifies computational setup, making it ideal for advanced users in distributed environments.